DEVELOPMENT OF BUDGETARY SLACK RESEARCH IN INDONESIA - Nisa, Rizka Fauziyatun; Rokhayati, Hijroh (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
This study aimed to provide an overview of the development of budgetary slack research in Indonesia. The research method was charting the field developed by Hesford et al. (2007). In this study, articles were classified based on topics, research methods, samples, and theories. The research samples were 161 articles published in 35 journals accredited by Sinta 1, 2, and 3 with 23 years of observation from 1999-2021. The results showed that for the research topic, the budget participation variable was the most widely used antecedent in research. Then as many as 157 articles used quantitative research methods, the most widely used samples were Local government work unit (SKPD) budget makers, and the most widely used theory in budgetary slack research was agency theory. Suggestions for further budgetary slack research are to use an experimental research design with research participants from professional accountants, managers, or employees who are directly involved in the budgeting process. In addition, it can examine several internal influence variables (moral reasoning, locus of control, religiosity, honesty, ethics, managerial trust, and motivation) and external influence variables (compensation scheme (clawback) and compliance pressure).